Enhancing Speaking Participation Through Project-Based Learning in EFL Classrooms - Lalu Ari Irawan; Ramli Ahmad (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Speaking skills continue to be a challenge for many Indonesian EFL learners, caused by anxiety, limited confidence, and teacher-centered practices. Although Project-Based Learning (PjBL) has been widely introduced to enhance communication and collaboration, the evidence on its effectiveness in improving speaking participation in Indonesian high schools is still limited. Therefore, this study aimed to investigate the effectiveness of PjBL in enhancing students’ active participation in English-speaking activities. Using a Classroom Action Research (CAR) design, the study involved 37 students of class XI IPS-5 at SMAN 1 Keruak during the 2024 academic year. Data were collected through observation sheets, teacher’s written reports, and student questionnaires, focusing on five indicators of speaking participation: asking questions, answering, engaging in discussions, expressing opinions, and delivering presentations. The findings show a noticeable improvement in students’ active participation recorded throughout the observation and the field notes. Students’ participation shifted from limited participation in cycle 1 to confident participation and full involvement during presentation by cycle 2. The questionnaire results revealed that from the 34 students, 100% reported increased confidence in speaking, over 90% indicated higher motivation and enjoyment, and 97% stated that PjBL helped them better understand the lesson. These outcomes illustrate that PjBL not only strengthens language skills but also supports confidence, motivation, and collaborative engagement. The findings have important implications for educators seeking to address the low speaking participation of English as Foreign Language (EFL) learners through the use of (PjBL).